Correlation of Vulvar Quality of Life Index with Sociodemographic and Clinical Features in Patients with Vulvar Dermatoses - Tumbal, Namita; YG, Anupama; Singh, Neha; HJ, Dadapeer (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Vulvar dermatoses encompass a spectrum of disorders affecting female genitalia, often causing significant physical discomfort and psychological distress. Social stigma and anatomical factors frequently delay presentation, impairing quality of life. The Vulvar Quality of Life Index is a validated tool to measure disease-specific impact. Objectives: To assess socio demographic and clinical features of vulvar dermatoses and evaluate impact on quality of life using Vulvar Quality of Life Index. Materials and Methods: In this cross-sectional study, 100 women presenting with vulvar complaints at tertiary hospital from July to December 2023 underwent clinical evaluation and completed the questionnaire. Associations between Vulvar Quality of Life Index scores and socio demographic/clinical variables were done. Results: The mean score was 17.48 ± 8.3, with 80% experiencing moderate impairment (score 14–23). Mean age was 42.8 ± 9.6 years; most participants were 41–50 years (31%). Age significantly correlated (p = 0.003), with women >50 years scoring higher (mean 19.24). Higher scores were observed in women with primary education (32%; CI 16.9–19.5; p = 0.14), married participants (84%; mean 17.9, CI 17.1–18.7; p = 0.209), housewives (69%; CI 17.3–19.1; p = 0.05), and rural residents (64%; CI 17.2–19.2; p = 0.09). Participants with diabetes or hypertension had a mean score of 18.8 (CI 13.3–24.3; p = 0.031). Infections were most common (61%; mean 17.2, CI 16.4–18.0), while immunobullous disorders had the highest burden (mean 22.3, CI 19.4–25.2; p = 0.001). Women with genital, skin, and oral lesions had higher scores (mean 21.0, CI 14.1–27.9; p = 0.114). ‘Activities of Daily Living’ was the most affected domain (51%; CI 17.63–19.37; p = 0.07). Limitation of the study were single-centre design and limited sample size, limiting generalizability. Conclusion: Vulvar Quality of Life Index effectively captures the multidimensional burden of vulvar dermatoses on physical, emotional, and social domains. Routine incorporation into clinical practice can guide treatment, monitor progression and enhance patient-centered care.